Preoperative Prevalence of and Risk Factors for Venous Thromboembolism in Patients with a Hip Fracture: An Indirect Multidetector CT Venography Study. (21st December 2016) - Shin, Won Chul; Woo, Seung Hun; Lee, Seung-Jun; Lee, Jung Sub; Kim, Choongrak; Suh, Kuen Tak
Abstract : Background: This retrospective cohort study investigated the prevalence of and risk factors for preoperative venous thromboembolism (VTE) in patients with a hip fracture and a delay of >24 hours from injury to surgery. Methods: This observational study included 208 patients with a hip fracture surgically treated at 1 university hospital between December 2010 and August 2014. Patients underwent indirect multidetector computed tomographic (MDCT) venography for preoperative VTE detection after admission. Overall VTE risk and median time from injury to CT scan were calculated. Age, sex, fracture type, time from injury to CT scan, body mass index, preinjury mobility score, previous anticoagulation treatment, previous hospitalization for VTE, varicose veins, and medical comorbidities were considered potential risk factors. Results: The prevalence of preoperative VTE was 11.1% (23 of 208 patients), including 12 patients with deep vein thrombosis alone, 7 patients with pulmonary embolism alone, and 4 patients with both. The mean time from injury to CT scan was 4.9 days. The delay from the time of injury to CT scan averaged 7.6 days for patients who developed preoperative VTE, compared with 4.2 days for patients who had not developed VTE. In the adjusted models, female sex, subtrochanteric fracture, pulmonary disease, cancer, previous hospitalization for VTE, and varicose veins were risk factors for VTE. The final multivariate logistic regression analysis demonstrated that female sex (odds ratio [OR] = 5.86; 95% confidence interval [CI] = 1.21 to 28.21), subtrochanteric fracture (OR = 22.17; 95% CI = 4.02 to 122.06), pulmonary disease (OR = 21.10; 95% CI = 5.35 to 83.21), and previous hospitalization for VTE (OR = 16.36; 95% CI = 3.41 to 78.43) increased the risk of VTE. Conclusions: Our findings show a high prevalence of preoperative VTE in patients with a hip fracture. Therefore, preoperative investigation for VTE should be routinely considered for patients in whom surgery is delayed for >24 hours. At this time, indirect MDCT venography seems to be effective and useful. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.